2015
DOI: 10.1016/j.devcel.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Vessel Pruning and Regression

Abstract: The field of angiogenesis research has primarily focused on the mechanisms of sprouting angiogenesis. Yet vascular networks formed by vessel sprouting subsequently undergo extensive vascular remodeling to form a functional and mature vasculature. This "trimming" includes distinct processes of vascular pruning, the regression of selected vascular branches. In some situations complete vascular networks may undergo physiological regression. Vessel regression is an understudied yet emerging field of research. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
247
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(253 citation statements)
references
References 113 publications
5
247
1
Order By: Relevance
“…Interestingly, they found that conditional Vhl-KO induced ectopic VEGF-A expression, but retinal blood vessel branching actually decreased, as was observed in the present study. Kurihara and colleagues found that diminished vascular branching resulted largely from vessel regression, which likely represents the vessel pruning phase of retina vascular maturation (41). In contrast, the conditional type 2B Vhl mutation generated in the current study (i.e., UBC CreER/+ Vhl fl/2B ) did not cause a decrease in network complexity, and arterial branching was in fact enhanced significantly at P5.…”
Section: Discussioncontrasting
confidence: 41%
“…Interestingly, they found that conditional Vhl-KO induced ectopic VEGF-A expression, but retinal blood vessel branching actually decreased, as was observed in the present study. Kurihara and colleagues found that diminished vascular branching resulted largely from vessel regression, which likely represents the vessel pruning phase of retina vascular maturation (41). In contrast, the conditional type 2B Vhl mutation generated in the current study (i.e., UBC CreER/+ Vhl fl/2B ) did not cause a decrease in network complexity, and arterial branching was in fact enhanced significantly at P5.…”
Section: Discussioncontrasting
confidence: 41%
“…The cellular aspects of this process have been summarized recently (Korn and Augustin, 2015;Ricard and Simons, 2015). In short, although apoptosis has been implicated in the regression of larger blood vessels, it turns out that smaller vessels are pruned by the reabsorption of ECs into the remaining vasculature.…”
Section: Pruning: Removing Vesselsmentioning
confidence: 99%
“…Potential responses include persistence on the denuded capillary wall, apoptosis and migration onto surviving nearby capillaries [25]. Moreover, signals determining the destiny of the underlying endothelium are not yet understood.…”
Section: The Importance Of Pericytesmentioning
confidence: 99%
“…Understanding the mechanisms that contribute to vasoregression is essential for its prevention, and physiological vasoregression acts as a good example from which we can learn about inborn programming that is reactivated during incipient disease stages. Novel, dynamic, high-resolution microscopic techniques used to study developing rodent vasculature have characterised vessel regression as being: (1) an adaptive response to the exponential growth curve of angiogenesis towards a vascular network matching metabolic and functional demands for maintenance; (2) a process selecting capillary branches for regression by still unknown triggers; and (3) a process involving endothelial cell apoptosis, migration and redeployment as phenotypes [25]. More specifically, the process of vasoregression has been conceptually divided into sequential steps: branch selection by flow dichotomy, vessel constriction, occlusion, endothelial retraction/apoptosis/reintegration and then resolution of the remaining matrix tube.…”
Section: The Importance Of Vasoregressionmentioning
confidence: 99%